"An opportunity to hope and dream": Disaster Politics and the Emergence of Possibility through Community‐Led Recovery. Issue 2 (30th September 2018) - Cretney, Raven
Abstract: Recent awareness of the role of neoliberalism in fostering tactics of de‐politicisation has cultivated recognition of a narrowing of democratic possibilities. Disaster, as a time of disruption can provoke a heightened awareness of dynamics of power and contestation. This provides a fertile ground to understand the possibility for de‐politicisation alongside that of resistance and hope. This paper weaves together and contextualises these ideas within a case study of community‐led disaster recovery in the city of Ōtautahi Christchurch in Aotearoa New Zealand following a series of devastating earthquakes in 2010 and 2011. In exploring the entangled relationship between crisis and hope I discuss how forms of de‐politicisation can emerge in the disaster context as well as the resistance that also emerges at the grassroots and everyday scale. I emphasise the need to see post politics as present‐yet‐incomplete alongside the potential for participatory and radical forms of social change at the grassroots scale.